2007
DOI: 10.1038/sj.bjc.6603995
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed pharmacokinetics and pharmacodynamics in a phase I/II study of doublet chemotherapy with vinorelbine: implications for further optimisation of pemetrexed schedules

Abstract: The purpose of this study was to investigate the utility of plasma pharmacokinetic and pharmacodynamic measures including plasma deoxynucleosides, homocysteine and methylmalonic acid concentrations in understanding the time course and extent of the inhibition of thymidylate synthase (TS) by pemetrexed in the context of a phase I/II combination study with vinorelbine. Eighteen patients received supplementation with folic acid and Vitamin B 12 1 week before beginning treatment with pemetrexed and vinorelbine adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Pemetrexed pharmacokinetic studies in NSCLC patients have suggested that thymidylate synthase inhibition is short-lived, especially with concurrent vitamin B 12 and folic acid supplementation, suggesting that an every 2-week schedule may be optimal [20,23]. Administration of accelerated doses of pemetrexed (500 mg/m 2 every 2 weeks) has been shown to be feasible and well tolerated in NSCLC patients [24].…”
Section: Discussionmentioning
confidence: 97%
“…Pemetrexed pharmacokinetic studies in NSCLC patients have suggested that thymidylate synthase inhibition is short-lived, especially with concurrent vitamin B 12 and folic acid supplementation, suggesting that an every 2-week schedule may be optimal [20,23]. Administration of accelerated doses of pemetrexed (500 mg/m 2 every 2 weeks) has been shown to be feasible and well tolerated in NSCLC patients [24].…”
Section: Discussionmentioning
confidence: 97%
“…The individualized adjustment would ensure each patient for greater efficiency while minimizing toxicity. Indeed, the pharmacokinetic data, published during the clinical development of pemetrexed [8], showed good correlation between plasmatic concentrations and toxicity, especially hematologic. On the other hand, inter-patients pharmacokinetic variability has also been described [9,10].…”
Section: Introductionmentioning
confidence: 90%
“…Subsequent hydrolysis of the phosphate moiety causes deoxyuridine efflux into the circulation. Therefore, plasma deoxyuridine has been regarded as a PD marker for systemic TS inhibition [18]. It was therefore of interest, to examine the effect of pemetrexed dosing on the above parameters in mononuclear cells.…”
Section: Resultsmentioning
confidence: 99%